Determination of Preoperative and Postoperative Serum Leptin, Ghrelin, Insulin, and Irisin Hormone Levels in Left Abomasum Displacement - Ergin Eğritağ, Hale; Büyükoğlu, Tülay; Yiğitarslan, Kürşad (Progress in Nutrition, 2022)
Background and aim: Left Displacement Abomasum (LDA) is a metabolic disorder associated with negative energy balance, especially in dairy cattle, and might cause economic losses. This study, it was aimed to evaluate the serum levels of insulin, leptin, ghrelin, and irisin hormones responsible for energy metabolism before and after the operation in Holstein cattle with LDA. Methods: For this purpose, cattle were divided into three groups (Group 1: Healthy, Group 2: Pre-operative, Group 3: Post-operative) with 8 animals in each group, and blood samples were collected. In serum samples, glucose, non-esterified fatty acid (NEFA), beta-hydroxybutyrate (BHBA), total protein, triglyceride, total cholesterol, and calcium levels were measured with an autoanalyzer. In addition, commercial kits measured serum insulin, leptin, ghrelin, and irisin hormone levels with the EIA method. Results: Preoperative serum glucose, NEFA, and BHBA levels were higher in cattle with LDA, and total protein and triglyceride levels were lower than in healthy animals (p<0.05). In cattle with LDA after the operation, these values ​​were similar to those of healthy animals. In hormone analysis, ghrelin, insulin, and irisin were found to be higher in animals with LDA, while leptin levels were found to be decreased (p<0.05). After the operation, the insulin levels of the cattle with LDA decreased below the pre-operative values; It was observed that leptin and irisin levels were increased (p<0.05). Conclusions: In cattle with LDA, increased ghrelin levels may be due to anorexic conditions; Increased insulin levels may be due to stress and negative energy balance. Decreased serum insulin levels in cattle after the operation suggested that it may be related to the insulin resistance state caused by the left displacement abomasum. Increased serum leptin can be considered an acute phase response to leptin, and an increase in serum irisin can be a marker of pain and stress.